Correlation and Path Analysis of Morphological Traits and Body Mass in Perca schrenkii - Qing Ji; Zhengwei Wang; Huale Lu; Huimin Hao; Syeda Maira Hamid; Qing Xiao; Wentao Zhu; Tao Ai; Zhaohua Huang; Jie Wei; Zhulan Nie (Fishes)
Perca schrenkii populations are experiencing significant declines, yet comprehensive morphological studies are still lacking. Understanding the relationship between morphological traits and body weight is crucial for conservation and breeding programs. We analyzed 13 morphological traits in 100 P. schrenkii specimens from Hamsigou Reservoir using correlation analysis, path analysis, and principal component analysis (PCA). Body weight exhibited the highest variability (CV = 39.76%). Strong correlations were observed between body weight and body length (R = 0.942), total length, and body width. A four-variable regression model explained 94.1% of body weight variation, with body length showing the strongest direct effect (path coefficient = 0.623). The first three principal components accounted for 76.687% of the total variance. Our findings demonstrate that BL, BW, BD, and ES can effectively predict body weight, providing valuable insights for the conservation and selective breeding of P. schrenkii.